2016
DOI: 10.1007/s00261-016-0702-2
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of peristalsis-related gastrointestinal streak artifacts with dual-energy CT: a patient and phantom study

Abstract: Objective The purpose of the study was to assess the ability of rapid-kV switching (rs) dual-energy computed tomography (DECT) to reduce peristalsis-related streak artifact. Methods rsDECT images of 100 consecutive patients (48 male, 52 female, mean age 57 years) were retrospectively evaluated in this institutional review board–approved study. Image reconstructions included virtual monochromatic 70 and 120 keV images, as well as iodine(-water) and water(-iodine) material decomposition images. We recorded the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 25 publications
(24 reference statements)
2
20
0
Order By: Relevance
“…This in turn causes them to appear in maximal severity in the water density image, as water also exhibits attenuation properties independent of X-ray energy within the diagnostic energy range (19). Correspondingly, they are largely absent in the iodine density image, as this image reconstruction shows projection data which exhibit a reduction in attenuation from low to high kVp.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This in turn causes them to appear in maximal severity in the water density image, as water also exhibits attenuation properties independent of X-ray energy within the diagnostic energy range (19). Correspondingly, they are largely absent in the iodine density image, as this image reconstruction shows projection data which exhibit a reduction in attenuation from low to high kVp.…”
Section: Discussionmentioning
confidence: 99%
“…Further study will be needed on these other DECT implementations. Fourthly, the introduction of other artifacts, such as beam hardening (28), by iodine density images were not evaluated. Fifthly, since topogram images are not routinely saved in our CT scans, we did not assess the value of topograms for predicting the value of DECT reconstructions to improve out-of-field artifacts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The first study by Lourenco et al [62] demonstrated a significant reduction in IC in bowel segments suffering from acute bowel ischemia. The second study by Winklhofer et al [63] demonstrated that peristalsis-related streak artifacts can be reduced using iodine maps (Studies shown in Table 4). Significant difference between squamous cell carcinoma and adenocarcinoma in both phases (nIC-A: p = 0.02, nIC-V: p = 0.00)…”
Section: Miscellaneous Applicationsmentioning
confidence: 99%
“…DECT and photon-counting, energy-discriminating (PCED) CT are two major types of “spectral” CT, in which the unique, energy-dependent attenuating characteristics of materials can provide new diagnostic information[13]. The most-published benefits of spectral CT are reduced image artifacts [1416], differentiation between tissue compositions [17], and improved detection and quantification of iodine- and barium-based contrast material concentrations [3] with a single pass of the CT scanner. The medical community is gradually embracing DECT for these benefits.…”
Section: Introductionmentioning
confidence: 99%